Clone candidates differentiation of grapevine Vitis vinifera'Škrlet bijeli' using aroma compounds detected by gas chromatography-mass spectrometry - Ivana Vladimira Petric; Tatjana Košmerl; Ivan Pejić; Veronika Kubanović; Emil Zlatić (Acta Agriculturae Slovenica)
The aim of this work was to investigate existence presence and stability of must specific aroma compounds (monoterpenes C13-norisoprenoids, C6-alcohols, alcohols, esters and carbonyl compounds) and which can be used to establish differences among clone candidates of 'Škrlet bijeli' (Vitis vinifera L.) grapevine variety. The compounds responsible for the varietal aroma profile were determined by gas chromatography- mass spectrometry (GC-MS), in must samples of ten clone candidates grown on two vineyard sites for three consecutive years. Significant variation among clone candidates is shown in 22 out of the total 35 identified aroma compounds. Significant impact of the vineyard site on the clone candidate’s aroma profile was identified. Differences in primary aroma compounds responsible for flavour of 'Škrlet bijeli' variety, linalool, terpinolen, nerol and α-terpineol, were not significant among clone candidates, while remarkable differences were established for β-damascenone. Contrary to expectation, monoterpene geraniol was not detected. Other identified aroma compounds (trans-ocimene, 2-methyl-1-butanol, myrcene, α-phelandrene, cis-ocimene and 3-methyl-1-butanol) noticeably less participate in total flavour description, but they still enable notable clone candidates discrimination.